Content Analysis Of Entrepreneurship Semester Learning Plan (RPS) Versus Character Education And Professional Ethics In The Heavy Equipment Engineering Study Program Of Padang State Polytechnic - Rusmardi Rusmardi (Al-Makki Publisher, 2023)
The study aims to compare the content of the Semester Learning Plan (RPS) of the Entrepreneurship and Character Education and Professional Ethics courses in the Heavy Equipment Study Program of the Padang State Polytechnic. This research is qualitative and based on the concept of